2003
DOI: 10.1597/1545-1569(2003)040<0356:lsoycw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Language Skills of Young Children With Unilateral Cleft Lip and Palate Following Infant Orthopedics: A Randomized Clinical Trial

Abstract: Children treated with IO during their first year of life produced longer sentences than non-IO children at the ages of 2(1/2) and 3 years. At 6 years of age, both groups presented similar expressive language skills. Hence, IO treatment did not have long-lasting effects on language development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
0
22
0
4
Order By: Relevance
“…The survey strategy resulted in 319 articles, of which 12 were qualified for the final analysis in the first survey (eight RCTs, four CCTs) (Karling et al, 1993;Ross and MacNamera, 1994;Chan et al, 2003;Konst et al, 2003b;Bongaarts et al, 2004;Prahl et al, 2005Prahl et al, , 2008Bongaarts et al, 2006;Masarei et al, 2007;Bongaarts et al, 2008;Barillas et al, 2009;Bongaarts et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The survey strategy resulted in 319 articles, of which 12 were qualified for the final analysis in the first survey (eight RCTs, four CCTs) (Karling et al, 1993;Ross and MacNamera, 1994;Chan et al, 2003;Konst et al, 2003b;Bongaarts et al, 2004;Prahl et al, 2005Prahl et al, , 2008Bongaarts et al, 2006;Masarei et al, 2007;Bongaarts et al, 2008;Barillas et al, 2009;Bongaarts et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Active palates were evaluated in two articles (Chan et al, 2003;Masarei et al, 2007) and passive plates in eight (Ross and MacNamera, 1994;Konst et al, 2003b;Bongaarts et al, 2004;Prahl et al, 2005Prahl et al, , 2008Bongaarts et al, 2006;Bongaarts et al, 2008;Bongaarts et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in the Dutchcleft study there were no observable effects on occlusion and jaw relationships at the ages of 4 and 6 years [63]. Evaluation of speech and language development showed that at one year of age, children who wore plates presented an enhanced production of alveolar sounds; however, at the age of 1.5 year, when the plate was no longer used, a limited effect on speech was observed [64]. At 30 months of age, the phonologic development of the orthopedic group was normal or delayed, while most children in the non-orthopedic group presented an abnormal development [65].…”
Section: Opinions Against Presurgical Orthopedicsmentioning
confidence: 96%